Reservoir rock diagnostics for water or hydrocarbon exploration : acoustic and electric fields interaction phenomena in geophysical research (seismoelectric & electroseismic effect) /: acoustic and electric fields interaction phenomena in geophysical research (seismoelectric & electroseismic effect). (2019) - Unknown
No abstract available